The Feasibility Analysis of Chinese Experimental Cultural Sites Setting: A Case Study of Wudang Mountain - Fang, Lin (Journal of Sinology (วารสารจีนวิทยา), 2014)
This article introduces an innovative course design on Chinese culture in teaching Chinese as a foreign language by means of exploring some experimental cultural sites which meet the Chinese experimental cultural sites setting requirement. According to the experiences from the activity of Confucius Institute Scholarship holders on Chinese culture, this paper selects Wudang Mountain, which vividly has the representiveness of Chinese culture, as the case study. After the field investigation and the contrast of Wudang culture, this paper screens out and sums up some perspectives which can symbolize Chinese culture, including religion, landscape and buildings, and martial arts. Moreover this paper provides an overall evaluation on infrastructure and culture dissemination, which is dealing with Teaching Chinese as a Foreign Language, to verify the feasibility to become a Chinese culture experimental site. Finally, as the Wudang Mountain case study, this article provides further suggestion on Chinese culture teaching, and survey on Chinese experimental sites construction.